Potential Crosstalk between Fructose and Melatonin: A New Role of Melatonin—Inhibiting the Metabolic Effects of Fructose - Francisco J. Valenzuela-Melgarejo; Claudia Caro-Díaz; Gerardo Cabello-Guzmán (International Journal of Endocrinology)
Increased consumption of energy-dense foods such as fructose-rich syrups represents one of the significant, growing concerns related to the alarming trend of overweight, obesity, and metabolic disorders worldwide. Metabolic pathways affected by fructose involve genes related to lipogenesis/lipolysis, beta-oxidation, mitochondrial biogenesis, gluconeogenesis, oxidative phosphorylation pathways, or altering of circadian production of insulin and leptin. Moreover, fructose can be a risk factor during pregnancy elevating the risk of preterm delivery, hypertension, and metabolic impairment of the mother and fetus. Melatonin is a chronobiotic and homeostatic hormone that can modulate the harmful effects of fructose via clock gene expression and metabolic pathways, modulating the expression of PPARγ, SREBF-1 (SREBP-1), hormone-sensitive lipase, C/EBP-α genes, NRF-1, PGC1α, and uncoupling protein-1. Moreover, this hormone has the capacity in the rat of reverting the harmful effects of fructose, increasing the body weight and weight ratio of the liver, and increasing the body weight and restoring the glycemia from mothers exposed to fructose. The aim of this review is to show the potential crosstalk between fructose and melatonin and their potential role during pregnancy.